2014
DOI: 10.1039/c4ob00032c
|View full text |Cite
|
Sign up to set email alerts
|

The development of catalytic nucleophilic substitution reactions: challenges, progress and future directions

Abstract: Bimolecular nucleophilic substitution reactions of alcohols are fundamentally important transformations in organic chemistry yet, to date, they are relatively underdeveloped with respect to catalysis. This Article describes the emerging area of catalytic SN2 reactions with specific emphasis on the design and development of phosphorus(V) and cyclopropenone-based catalytic SN2 reactions of alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(50 citation statements)
references
References 116 publications
0
48
0
2
Order By: Relevance
“…As observed for [ 5 ]Cl, 31 P and 13 C NMR spectra of [ 6 ]Cl confirmed its cationic character as well as the direct linkage of the phosphonium moiety to the cyclopropene ring ( δ P = 30.4 ppm (s); δ C = 52.4 ppm, (d, 1 J CP = 109.7 Hz)) (Schemeà). It should be noted that if spectroscopic data of [ 5 – 6 ]Cl are here in favor of a cyclopropenic structure, 3‐halogenocyclopropenes are known to be more or less displaced to their cyclopropenium form depending on the ability of the halide ion to dissociate from the cation …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As observed for [ 5 ]Cl, 31 P and 13 C NMR spectra of [ 6 ]Cl confirmed its cationic character as well as the direct linkage of the phosphonium moiety to the cyclopropene ring ( δ P = 30.4 ppm (s); δ C = 52.4 ppm, (d, 1 J CP = 109.7 Hz)) (Schemeà). It should be noted that if spectroscopic data of [ 5 – 6 ]Cl are here in favor of a cyclopropenic structure, 3‐halogenocyclopropenes are known to be more or less displaced to their cyclopropenium form depending on the ability of the halide ion to dissociate from the cation …”
Section: Resultsmentioning
confidence: 99%
“…The two different structures obtained by modifying only a substituent (Ph vs. Mes) on the starting cyclopropene raise questions about the mechanism of formation of bis(phosphonium) salts [ 7 – 8 ](OTf) 2 . Assuming in both series an equilibrium between the two covalently bonded cationic chlorocyclopropenes [ 5 – 6 ]Cl and [ 5a – 6a ]Cl via corresponding 3‐triphenylphosphoniocyclopropenium intermediate, the formation of bis(phosphonium) salts [ 7 – 8 ](OTf) 2 can be tentatively rationalized by the existence of steric and electrostatic constraints.…”
Section: Resultsmentioning
confidence: 99%
“…In 2009, Lambert and co-workers reported that cyclopropenium ions,b ecause of their unique aromatic character, [35] possessed the ability to activate alcohols towards efficient nucleophilic displacement. [9] This mechanism of activation (Scheme 10) exploited the equilibrium between 3,3-dichlorocyclopropene (83)a nd the aromatic chlorocyclopropene chloride salt 84 as ar esult of association and disassociation of an anion, as occurs on the parent systems 81 and 82.C yclopropenium salt 84 was subjected to nucleophilic attack by an alcohol, thereby resulting in the presumed reactive ether intermediate 86,which is in equilibrium with its rearomatized form 87 upon dissociation of the chloride anion.…”
Section: Novel Reactions Promoted By Cyclopropenium Ionsmentioning
confidence: 99%
“…[7] OBrien and co-workers disclosed the first example of aM itsunobu reaction that is catalytic in phosphine in the patent literature, [8] and optimization of this reaction is heavily desired. [4,9] Herein we report the development and optimization of aM itsunobu reaction catalytic in phosphorus utilizing dibenzophosphole and phospholane precatalysts 1 and 2 (Scheme 1B), inspired by the development of the catalytic Appel, [10a] Staudinger, [10b] and Wittig [11] reactions.W et hen combined this catalytic cycle with the Taniguchi iron-phthalocyanine catalytic system to generate the first fully catalytic Mitsunobu reaction (Scheme 1A). Chemoselective reduction of the phosphine oxide product back to the phosphine in the presence of ar eactive azo compound is required in order to complete the phosphine catalytic cycle.W ei nitially investigated dibenzophosphole oxide 1 as ap recatalyst due to its facile reduction by silanes and its ability to tune the catalyst through modification of the aryl rings.…”
mentioning
confidence: 99%
“…[2] However, the Mitsunobu reaction is highly underutilized in process chemistry and manufacturing due to arduous purification from by-products and poor atom economy. [3] Although several innovative reagents have been developed that can be removed by liquid-liquid or solid-liquid extractions to facilitate purification, [4] the ideal Mitsunobu reaction would be catalytic in phosphine and azocarboxylate,a nd use innocuous reagents to recycle these catalysts. [5] Toward this goal, Toyand co-workers rendered the Mitsunobu catalytic in the azocarboxylate using PhI(OAc) 2 to oxidize the hydrazine by-product [6] whereas Taniguchi and co-workers developed an iron(II) phthalocyanine catalytic system employing oxygen as the terminal oxidant.…”
mentioning
confidence: 99%